2014
DOI: 10.1186/2045-5380-4-4
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioural Inhibition System, anxiety and hippocampal volume in a non-clinical population

Abstract: BackgroundAnimal studies have suggested that the hippocampus may play an important role in anxiety as part of the Behavioural Inhibition System (BIS), which mediates reactivity to threat and punishment and can predict an individual’s response to anxiety-relevant cues in a given environment. The aim of the present structural magnetic resonance imaging (MRI) study was to examine the relationship between individual differences in BIS and hippocampal structure, since this has not received sufficient attention in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 74 publications
4
35
0
Order By: Relevance
“…PTSD) or simply due to trauma histories, other studies have demonstrated that elevated levels of glucocorticoids may lead to hippocampal diminution in non-human primates [29]. In a non-clinical sample, Levita et al [30] found a positive relationship between hippocampal volume (lateralized to the right hemisphere) and behavioural inhibition and suggested that any change to hippocampal volume, structural or functional, may serve as a diathesis for anxiety-related symptomatology.…”
Section: Traumatic Brain Injury and Depressionmentioning
confidence: 98%
“…PTSD) or simply due to trauma histories, other studies have demonstrated that elevated levels of glucocorticoids may lead to hippocampal diminution in non-human primates [29]. In a non-clinical sample, Levita et al [30] found a positive relationship between hippocampal volume (lateralized to the right hemisphere) and behavioural inhibition and suggested that any change to hippocampal volume, structural or functional, may serve as a diathesis for anxiety-related symptomatology.…”
Section: Traumatic Brain Injury and Depressionmentioning
confidence: 98%
“…We can speculate that the difficulty of the Hard NoGo trials may have been frustrating and may have activated emotional circuits related to anxiety. Previous studies have shown that greater HIP volume was associated with high scores on the sensitivity to punishment scale (Levita et al, 2014) and that hippocampal activation was related to monitoring of threat level during a human approach-avoidance task that emulated rodent anxiety paradigms (Bach et al, 2014). Thus, an alternative interpretation of our results would be that stronger control from MFG to HIP may have been related to anxiety during Hard NoGo than during Easy NoGo.…”
Section: Discussionmentioning
confidence: 59%
“…[22,26,41]. The hippocampal atrophy is correlated with Alzheimer's disease and mild cognitive impairment for the right hippocampus [49].…”
Section: Discussionmentioning
confidence: 99%
“…Malformation, disorder or damage of the HF have a great importance in the pathogenesis, or consequences, of the variety of the neurological and psychiatric disorders, e.g. the epilepsy, schizophrenia, amnesia, depression, anxiety, posttraumatic stress, aging, Alzheimer's and Parkinson's disease [14,26,37,38,41,42,49]. Even the slightest volume changes, which can be identified by modern imaging techniques, may indicate certain neuropathology or pathophysiology in this region.…”
Section: Introductionmentioning
confidence: 99%